Identification and isolation of proteins found only in plants with citrus decline - Vilela Paiva, Luciano; de Souza, Maurício; Lopes, Maurício Antônio; Paiva, Edilson (Pesquisa Agropecuaria Brasileira, 1997)
Measurement of Zn accumulation in the trunk wood and the water syringe absorption test are the standard tests for diagnosis commonly used to distinguish the trees affected by "citrus decline" from other anomalies that also cause degeneration of citrus plants. However, these tests only give positive results in advanced stages of the disease. The objective of this work was to identify proteins present only in plants with "citrus decline". The plants used were ’Valência’ orange trees with the ’Rangpur lime’ as rootstock with and without visual symptoms. Two proteins were characterized and isolated (26 and 23 KD) through electrophoresis, which were found only in plants with "citrus decline". For the first time in Brazil these proteins were linked to "citrus decline".